Nieformalne związki jedno i dwupłciowe jako alternatywne formy życia małżeńsko-rodzinnego. Analiza jakości i stabilności relacji - Jankowiak, Barbara (Wydawnictwo Naukowe UAM, 2013)
This thesis presents the characteristics of alternative forms of marriage and family life with special consideration of cohabitation and homosexual relations. These untraditional kinds of partnership relations are more and more common and become new socialization patterns. An analysis was carried out of the satisfaction and stability of informal same- and different sex relations and a comparison of these relations was made to the intimate relations of marriages in order to establish whetherfunctioning in relations of this kind is as valuable as being married. Polish and foreign studies so far prove that many relation characteristics such as love, happiness, stability, quality, or communication are not very different for various sexual orientation relations. Simultaneously, a greater stability of formal relationships as compared to common law ones was indicated.
Informal same-sex and Informal same-sex and and stability of relations
Keywords: homosexual relationships; cohabitation relations; marriages; relationship quality; relationship stability